2015
DOI: 10.1142/s021773231550073x
|View full text |Cite
|
Sign up to set email alerts
|

New realizations of 𝒩 = 2l-conformal Newton–Hooke superalgebra

Abstract: By applying Niederer-like transformation, we construct a representation of the N = 2 l-conformal Newton-Hooke superalgebra for the case of a negative cosmological constant in terms of linear differential operators as well as its dynamical realization. Another variant of N = 2 supersymmetric Pais-Uhlenbeck oscillator for a particular choice of its frequencies is proposed. The advantages of such realizations as compared to their analogues introduced in [J. Math. Phys. 53 (2012)

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…where ǫ ij is the Levi-Civitá symbol with ǫ 12 = 1. Symmetry structure intrinsic to the model (1) allows one to construct an N = 2 supersymmetric generalization of this system with the aid of Niederer-like coordinate transformations [15,35]. The action functional associated with this extension reads…”
Section: The Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…where ǫ ij is the Levi-Civitá symbol with ǫ 12 = 1. Symmetry structure intrinsic to the model (1) allows one to construct an N = 2 supersymmetric generalization of this system with the aid of Niederer-like coordinate transformations [15,35]. The action functional associated with this extension reads…”
Section: The Modelmentioning
confidence: 99%
“…The configuration space of this model involves the real bosonic coordinates x i , the fermionic coordinates ψ i ,ψ i , which are complex conjugates of each otherψ i = ψ * i , and real extra bosonic coordinates z i . The model (2) is invariant under the supersymmetry transformations of the form [15]…”
Section: The Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, in [20], [21] an N = 2 supersymmetric extension of the PU oscillator has been constructed. It has been shown that the invariance of the model under time translations implies unbounded from below spectrum.…”
Section: Introductionmentioning
confidence: 99%